A COMPARATIVE ANALYSIS OF JUGGLING SKILL BETWEEN SEPAK RAGA AND BULU AYAM - Mohamad Razali, Abdullah; Hafizan, Juahir; N. A., Kosni (2018)
The uses of sepak takraw ’s ball for daily training for children might cause injury, while contact between the foot and ball due to hard and heavy structure. This study aims to examine the differences of kinematic juggling between sepak raga and bulu ayam. Eight participants within the age 13.63 (±0.52) years old were asked to perform 20 trials of sepak sila and s epak kuda juggling using raga ball and bulu ayam . Digital Motion Analysis software was used to analyze the kinematics parameters. One-way repeated measure ANOVA was implemented to examine the differences between the sepak raga and bulu ayam . The finding shows that there are no significant differences of kinematic juggling between sepak raga and bulu ayam in sepak sila juggling skills as well as sepak kuda juggling skills (p > 0.05). The young athlete could choose either raga ball or bulu ayam for skill acquisition depending on their comfort.